Peningkatan hasil belajar peserta didik dengan pendektan Teaching At The Right Level (TARL) pada pembelajaran matematika kelas VII - Jaka Wisnu Wardana; Lilik Ariyanto; Purwanto (Pascasarjana Universitas PGRI Semarang, 2024)
This research aims to improve students' mathematics learning outcomes on line and angle materials. This type of research is a Classroom Action Research conducted at SMP N 6 Semarang in the even semester of the 2023/2024 school year through the Teaching at the Right Level (TaRL) approach. This research was conducted with two cycles. The research subjects were students of class VII B SMP N 6 Semarang. The research instruments used were learning tools, evaluation/reflection sheets. Data collection techniques in this study were tests in the form of description questions given to students at the end of each cycle to determine the learning outcomes of students. This research uses quantitative descriptive analysis techniques. Based on data analysis, it was found that by using the TaRL approach on line and angle material, there was an increase in learning outcomes, namely pre-cycle by 0%, cycle I by 11.76%, and cycle II by 88.23%. It can be concluded that the application of the TaRL approach to line and angle material can improve the learning outcomes of students in the cognitive aspect.